(untitled) (Research, Society and Development, 2021)
Objectives: Search for evidence on the effectiveness of iontophoresis in the healing of chronic wounds, as well as verify the parameterization used. Methods: Searches for articles were performed in the following databases: PubMed, Virtual Health Library, SciELO, PEDro, CAPES Theses and Dissertations Catalog - Brazil, Summaries of Brazilian Journals and the Brazilian Digital Library of Tests and Dissertations, with publication period from February 2011 to March 2021. The studies were analyzed by two authors independently using the eligibility criteria adopted in the study. Results: After the selection process, 4 articles remained, which highlight that an intophoresis can be effective in the treatment of chronic wounds and that this resource applied in conjunction with conventional medical treatment enhances the healing process in individuals with chronic wounds. Conclusion: An iontophoresis presentation effective in healing in patients with chronic wounds.